Aerospace Technologies Advancements - Arif, Thawar T. (IntechOpen, 2010)
Space technology has become increasingly important after the great development and rapid progress in information and communication technology as well as the technology of space exploration. This book deals with the latest and most prominent research in space technology. The first part of the book (first six chapters) deals with the algorithms and software used in information processing, communications and control of spacecrafts. The second part (chapters 7 to 10) deals with the latest research on the space structures. The third part (chapters 11 to 14) deals with some of the latest applications in space. The fourth part (chapters 15 and 16) deals with small satellite technologies. The fifth part (chapters 17 to 20) deals with some of the latest applications in the field of aircrafts. The sixth part (chapters 21 to 25) outlines some recent research efforts in different subjects.